USE OF RAPD MARKERS OPTIMIZES THE SELECTION OF SOURCE MATERIAL OF SWEET PEPPER (CAPSICUM ANNUUM L.) IN BREEDING FOR HETEROSIS - M. N. Shapturenko; L. A. Tarutina; T. V. Pechkovskaya; L. A. Mishin; L. V. Khotyleva (Вавиловский журнал генетики и селекции, 2014)
RAPD analysis of sweet pepper lines of various ecogeographical origins was made to study DNA screening efficiency for hybrid breeding. Genetic distances among parental lines were calculated. The collection was classified by UPGMA. Hybridization of polymorphic genotypes was carried out in 5 × 5 diallel cross. The combining ability of lines and the F1 heterosis effect were evaluated. Combinations with high levels of heterosis for performance traits were revealed. The contributions of additive and dominant genes to the realization of the genetic potential of parental lines were determined. Our study showed that the specific combining ability of lines of the sweet pepper collection was more important for the formation of heterosis than the general combining ability. Positive correlations between DNA marker distances of parents and heterosis degree were found for some performance traits, however, their levels were low. We plan seeking specific DNA loci that would be positively associated with hybrid performance.